Synthesis and Crystal Structure of New Pyridyl Derivative - Ge, Xinping; Li, Wei; Hao, Fuying; Li, Shengli; Jin, Feng; Zhou, Hongping (Asian Journal of Chemistry, 2014)
A pyridyl derivative with four stereo centers has been prepared by an efficient synthetic method based on a solvent-free reaction. The structure was characterized by elemental analyses, IR, 1H NMR, mass spectra and single crystal X-ray diffraction. The crystal structure shows that the cyclohexyl group is a chair conformation and three intramolecular hydrogen bonds generate the trimer.